Two patients with novel missense mutation in the purine nucleoside phosphorylase gene without serious or recurrent infections. Issue 1 (26th October 2015) - Kiykim, Ayca; Simsek, Isil Eser; Kiykim, Ertugrul; Karakoc‐Aydiner, Elif; Baris, Safa; Ozen, Ahmet Oguzhan; Aydogan, Metin; Santisteban, Ines; Hershfield, Michael; Barlan, Isil
Abstract: Purine nucleoside phosphorylase (PNP) deficiency is characterized by T – B + NK + combined immune deficiency, presenting with neurological deterioration and recurrent infections. PNP is an essential enzyme taking a part in the purine salvage pathway, converting inosine to hypoxanthine, and guanosine to guanine reversibly. We described two patients with PNP deficiency caused by a novel point mutation in exon 5: c.593 C>T, predicting the p.P198L amino acid substitution. Both patients presented with developmental delay and severe lymphopenia without any serious recurrent infections. Children with developmental delay and hypouricemia should be screened for PNP deficiency, especially in the presence of lymphopenia.